The Influence Of Taxpayer Knowledge, Tax Socialization And Taxpayer Compliance On Taxpayer Compliance In Time Pandemic Covid-19 - Ida Ayu Pradnya Kusuma DEWI; Ni Wayan SITIARI; Cokorda Krishna YUDHA (Journal of Governance, Taxation and Auditing, 2022)
This study aims to determine the effect of tax knowledge, tax socialization and tax sanctions on taxpayer compliance. The population in this study is the MSME corporate taxpayer in KPP Pratama North Badung, with the sample using as many as 100 respondents. The data analysis technique used in this research is Multiple Linear Regression, F Coefficient, Determination Test and t-Test. Based on the results of the study, it can be seen that tax knowledge has a positive and significant effect on taxpayer compliance, tax socialization has a significant positive effect on taxpayer compliance and tax sanctions have a significant positive effect on taxpayer compliance. The magnitude of the influence of the independent variable on tax knowledge is 55.4%